0

# How do you solve 2x^2+3x-2=0

How do you solve 2x^2+3x-2=0

Can u explain how u got the (2x) / 2 = (1) / 2

### 3 Answers by Expert Tutors

Evan W. | Mechanical Engineer: Tutoring physics, math, and statsMechanical Engineer: Tutoring physics, m...
5.0 5.0 (4 lesson ratings) (4)
0

If you get a more difficult polynomial, you can always use the quadratic equation:

x = (-b +/- sqrt(b^2 -4ac))/2a

where you have ax^2 + bx + c

so a=2, b=3, c=-2

x=(-3+/- sqrt(3^2-(4(2)(-2)))/2(2)

x=(-3+/- sqrt(9+16))/4

x=(-3+/-5)/4

x=-8/4=-2  and x=2/4 = 1/2

x= -2 and 1/2

Olga S. | Math made easy, Math made fun!Math made easy, Math made fun!
4.7 4.7 (106 lesson ratings) (106)
0

Hi Jasmine,

Solving quadratic equation is a big part of Algebra 1 course.

One of the methods is to use   Zero Product Property: if a product equal zero then one of the factors should be equal zero. It means that if a×b=0 then a=0 or b=0.

In order to use Zero Product Property for your equation you need to rewrite left side of the equation in factored form.

Since you are asking about solving quadratic equation you should know how to factor a trinomial. I will refresh your memory anyway. There is a nice 'grouping method' for factoring.

If you have trinomial 2x2+5x-3. First you want to find product of first and third term coefficients: 2×(-3)=-6  Now you need to find two numbers  that give you -6 when multiplied and 5 when added. This is like guess and check game. Out of all possible pairs of factors for -6 (-1 and 6, 1 and -6, -2 and 3, 2 and -3) only -1+6=5. Next step is to rewrite 5x as -1x+6x.

2x2+5x-3= 2x2+(-1)x+6x-3

Now use distributive property

2x2+(-1)x+6x-3=x(2x-1)+3(2x-1)

2x-1 is a common factor, so we can use distributive property again

(2x-1)(x+3) a factored form of trinomial 2x2+5x-3

To solve equation 2x2+5x-3=0, we need to solve equation (2x-1)(x+3)=0.

Now we are ready to apply Zero Product Property: if product of (2x-1) and (x+3) equal zero then

2x-1=0  or  x+3=0

Inctead of solving one quadratic equation you need to solve two easy equations. Both solutions will be solutions of original equation.

If you follow my steps you can solve your equation by yourself. Good luck.

Olga

Tamara J. | Math Tutoring - Algebra and Calculus (all levels)Math Tutoring - Algebra and Calculus (al...
4.9 4.9 (51 lesson ratings) (51)
0

2x2 + 3x - 2 = 0

Here you have a quadratic equation with one unknown variable (x). Since the equation is set equal to 0, we solve for it by factoring the left hand side of the equation and then apply the zero product property to solve for the unknown variable (x).

Factoring:          2x2 + 3x - 2 = 0

(2x - 1)(x + 2) = 0

Zero product property:          (2x - 1)(x + 2) = 0

2x - 1 = 0              AND            x + 2 = 0

2x - 1 = 0                              AND             x + 2 = 0

+ 1    + 1                                                  - 2     - 2

______________                                      _______________

2x = 1                                                        x = -2

(2x) / 2 = (1) / 2

x = 1/2

Thus, the solution to this equation is:       x = 1/2     and     x = -2